Conceptual Misunderstandings in the Structuration of Anti-crisis Economic Policy: Lessons from the Greek Case - Charis Vlados; Nikos Deniozos; Demosthenes Chatzinikolaou; Michail Demertzis (Universitas Muhammadiyah Yogyakarta, 2018)
The objective of this study is to clarify the prevailing vague and sometimes misguided understanding regarding the articulation of economic policy, especially in the context of socioeconomic systems in structural crisis.The distortions of the economic policy are keep reproducing and spreading usually because of three disorientating conceptual sources: a) the view of economic policy supposedly as a de-ideologized construction, or as a de-technicalized voluntarism, b) the view of economic policy supposedly as a de-strategized synthesis, c) the view of economic policy as a supposedly automatic, ungradated and timeless procedure.For a socioeconomic system to exit from its crisis and by applying these concepts to the Greek case, we see as a prerequisite the interruption of this vicious circle of misconceptions, towards the trajectory of a virtuous circle of valid understanding the meaning of economic policy.